1998
DOI: 10.1177/026988119801200107
|View full text |Cite
|
Sign up to set email alerts
|

A role for sensitization in craving and relapse in cocaine addiction

Abstract: Sensitization to cocaine refers to the behavioral model of cocaine addiction where the motor stimulant effect of cocaine is augmented for months after discontinuing a regimen of repeated cocaine injections. There has been speculation that the neuroadaptations mediating this sensitization phenomenon may, in part, underlie the behavioral changes produced by chronic cocaine abuse, including paranoia, craving and relapse. Criteria are proposed that may assist in determining which neuroadaptations are most relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(127 citation statements)
references
References 26 publications
2
125
0
Order By: Relevance
“…Repeated cocaine administration can induce persistent behavioral changes that may reflect drug-induced neuronal plasticity (Robinson and Berridge 1993;Kalivas et al, 1998;Vanderschuren and Kalivas, 2000), and the D1 receptor has been shown to be critical in mediating cocaine-induced long-lasting behavioral changes (Xu et al, 2000;Zhang et al, 2002). We used the microarray method to identify chronic cocaine-induced gene expression differences in the two groups of mice 24 h after cocaine withdrawal.…”
Section: Resultsmentioning
confidence: 99%
“…Repeated cocaine administration can induce persistent behavioral changes that may reflect drug-induced neuronal plasticity (Robinson and Berridge 1993;Kalivas et al, 1998;Vanderschuren and Kalivas, 2000), and the D1 receptor has been shown to be critical in mediating cocaine-induced long-lasting behavioral changes (Xu et al, 2000;Zhang et al, 2002). We used the microarray method to identify chronic cocaine-induced gene expression differences in the two groups of mice 24 h after cocaine withdrawal.…”
Section: Resultsmentioning
confidence: 99%
“…Second, a causal link between the long-term expression of behavioral sensitization and sensitization of the mesolimbic DA system has been suggested (Kalivas and Duffy, 1993a;Vanderschuren and Kalivas, 2000). The failure of repeated ETOH intoxication to induce sensitization of the accumbens DA response suggests that repeated exposure to different drugs of abuse does not necessarily result in a common final neuroadaptation that triggers compulsive drug use or, alternatively, and contrary to a widely held notion, this common final neuroadaptation does not involve sensitization of the mesolimbic DA system (Kalivas et al, 1998;Robinson and Berridge, 2001). Of course, the fact that we failed to see sensitization of the DA response does not prove that it would not occur under other experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, referred to as behavioral sensitization, is manifested in rodents as an increase in drug-evoked locomotor activity after repeated drug administration. Behavioral sensitization is proposed to result from some of the same neuroadaptations that are triggered by repeated drug exposure and that lead to the development of compulsive drug use (Kalivas et al, 1998). One neuroadaptation that has received considerable attention involves the effects of repeated drug experience on the mesoaccumbal dopaminergic system.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral sensitization refers to the progressive increase in the locomotor stimulant properties of a drug following chronic drug administration and is considered a long-term neuro adaptation important for the maintenance of drug dependence (Kalivas et al, 1998;Robinson and Berridge, 1993;Vanderschuren et al, 1999). Cocaine-induced sensitization occurs through the stimulation of D 1 receptors on cortical afferents to the VTA, which, in turn, induces glutamate release.…”
Section: Cocaine-induced Sensitizationmentioning
confidence: 99%